Physicochemical and bioactive properties of cold press wild plum (Prunus spinosa) and sour cherry (Prunus cerasus) kernel oils: fatty acid , sterol and phenolic profile - Atik, Ilker; Karasu, Salih; Sevik, Ramazan (INNOVHUB SSI-AREA SSOG, 2022)
This study aimed to determine some physicochemical and bioactive properties of oils obtained by the cold press method from wild plum and sour cherry kernels. The peroxide (PV), free fatty acidity (FFA), total phenolic contenent (TPC), and antioxidant capacity (AC) values of the wild plum kernel and sour cherry kernel oils were determined to characterise physicochemical properties. PV and FFA values were found to be 1.19 meq O-2/kg and 0.129% in wild plum oil, while the same values were 1.70 meq O-2/kg and 6.60% in sour cherry oil, respectively, indicating that FFA and PV values were in the range of acceptable limit. The TPC and AC values were determined as 28.32 and 33.65 GAE/g of extract, and 1.44 and 1.86 mmol TE/g of extract for wild plum kernel oil and sour cherry kernel oil, respectively. Oleic (72.72%) and linoleic acids (42.42%) were found as major fatty acids for wild plum and sour cherry oils, respectively. In terms of sterol composition, 8-sitosterols (2509.93 and 6018.27 ppm) were found at the highest levels in both kernel oils. Vanillin (4.70 ppm) was established as the major phenolic component in wild plum kernel oil, while benzoic acid (79.7 ppm) was found as the most constituent in sour cherry kernel oil. Total tocopherol concentrations of samples were 728.86 and 224.43 ppm, respectively. As a result, it has been revealed that the kernels of these fruits, which are abundant as fruit juice industrial waste, can be processed into vegetable oil and used as a source of edible oil.
Keywords: Wild plum; sour cherry; cold press; oil; DIFFERENT EXTRACTION; SEED; POMEGRANATE; CULTIVAR; APRICOT; IMPACT; FRUITS; Food Science & Technology